2023
DOI: 10.3389/fmicb.2023.1154344
|View full text |Cite
|
Sign up to set email alerts
|

Fungal succession in decomposing ash leaves colonized by the ash dieback pathogen Hymenoscyphus fraxineus or its harmless relative Hymenoscyphus albidus

Abstract: IntroductionThe ascomycete Hymenoscyphus fraxineus, originating from Asia, is currently threatening common ash (Fraxinus excelsior) in Europe, massive ascospore production from the saprotrophic phase being a key determinant of its invasiveness.MethodsTo consider whether fungal diversity and succession in decomposing leaf litter are affected by this invader, we used ITS-1 metabarcoding to profile changes in fungal community composition during overwintering. The subjected ash leaf petioles, collected from a dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…It has been shown that H. fraxineus can survive for months in air-dried petioles covered with a pseudosclerotial layer (Gross and Holdenrieder 2013), and that its ascomata can be formed also on older petioles, for up to five growing seasons after the leaves have been shed (Kirisits and Schwanda 2015). Fungal community profiling of overwintered ash leaf petioles showed that pseudosclerotial areas are dominated by H. fraxineus and possess very low fungal diversity in comparison to petiole regions that have not been secured by the pathogen pseudosclerotial plate (Kosawang et al 2023).…”
Section: Saprotrophic Phasementioning
confidence: 99%
“…It has been shown that H. fraxineus can survive for months in air-dried petioles covered with a pseudosclerotial layer (Gross and Holdenrieder 2013), and that its ascomata can be formed also on older petioles, for up to five growing seasons after the leaves have been shed (Kirisits and Schwanda 2015). Fungal community profiling of overwintered ash leaf petioles showed that pseudosclerotial areas are dominated by H. fraxineus and possess very low fungal diversity in comparison to petiole regions that have not been secured by the pathogen pseudosclerotial plate (Kosawang et al 2023).…”
Section: Saprotrophic Phasementioning
confidence: 99%